Intramolecular Frustrated Lewis Pair with the Smallest Boryl Site: Reversible H2 Addition and Kinetic Analysis1. (17th December 2014) - Chernichenko, Konstantin; Kótai, Bianka; Pápai, Imre; Zhivonitko, Vladimir; Nieger, Martin; Leskelä, Markku; Repo, Timo
Abstract: Ansa ‐aminoborane1 ( ortho ‐TMPC6 H4 BH2 ; TMP=2, 2, 6, 6‐tetramethylpiperid‐1‐yl), a frustrated Lewis pair with the smallest possible Lewis acidic boryl site (BH2 ), is prepared. Although it is present in quenched forms in solution, and BH2 represents an acidic site with reduced hydride affinity, 1 reacts with H2 under mild conditions producing ansa ‐ammonium trihydroborate2 . The thermodynamic and kinetic features as well as the mechanism of this reaction are studied by variable‐temperature NMR spectroscopy, spin‐saturation transfer experiments, and DFT calculations, which provide comprehensive insight into the nature of1 .